Animating human athletes - Hodgins, J. K.; Wooten, W. L.; Brogan, D. C.; O`Brien, J. F. (SIGGRAPH '95 Proceedings of the 22nd annual conference on Computer graphics and interactive techniques, 1995)
The paper describes algorithms for the animations of male and female models performing three dynamic athletic behaviors: running, bicycling and vaulting. We animate these behaviors using control algorithms that cause a physically realistic model to perform the desired maneuver. For example, control algorithms allow the simulated humans to maintain balance while moving their arms, to run or bicycle at a variety of speeds, and to perform two vaults. For each simulation we compare the computed motion to that of humans performing similar maneuvers. We perform the comparison both quantitatively through real and simulated video images and qualitatively through simulated and biomechanical data.